Financial Analysis of Green Detergent as A Water-Friendly Solution In Indonesia - Dian Masita Dewi; Agni Danaryanti (Publikasi Indonesia, 2022)
The most crucial global issue discussed at the Fourth Intergovernmental Review Meeting on the Implementation of the Global Program of Action for the Protection of the Marine Environment from Bali Land Based Activities (IGR-4) in 2018 is the danger of detergent. Up to 45% of Indonesia’s rivers are in the category of being heavily polluted by detergent. Furthermore, Enzymatic Eco Detergent is a new, renewable, and innovative biodegradable product made from vegetable surfactants based on palm oil (MES). It is also enriched with organic enzymes produced by simple biotechnology from processing organic waste, such as fruits and vegetable peels, based on garbage enzyme/eco-enzyme. And it also has excellent potential to be developed on a micro business scale (Start-up). As a new product, conducting a business feasibility analysis is necessary to reduce the risk of failure or loss. Therefore, this study aims to analyze the feasibility of the Eco Detergent factory start-up business with a capacity of 12,000 liters per year based on a financial analysis involving the Payback Period, Net Present Value, Internal Rate of Return, and Return on Investment. The data obtained were analyzed using Microsoft Excel 2013 software. The result showed that the payback period (PP) is three years (2 years and 3 months) faster than the project age of 5 years, hence the Green detergent start-up project,